Perspectives on euthanasia : a qualitative investigation of a selected sample of health professionals and lay people : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education - Tielmans, Wilma (Massey University, 2004)
As a topic the practice of euthanasia is regularly in the news in New Zealand. It is also practised covertly such as withdrawal of treatment, mercy killing and withholding of futile treatment. Knowledge and perceptions regarding these practices differ. This study explores the possible difference(s) in knowledge base between health professionals and the general population in respect to euthanasia. This project, designed as a qualitative study was guided by the following research question: What is the knowledge base and decision-making process between lay people and health professionals regarding the practice of euthanasia? The research was done through a qualitative approach by means of interview. In total fourteen participants from the greater Wellington area were involved in the research project, seven participants representing health professionals and seven participants representing the general population. The interview was designed to capture the knowledge base and insights and values of individuals with respect to euthanasia. Comparing the group of health professionals with the group of individuals from the general population resulted in some quantitative data. The study initially looked at descriptive data pertaining to the topic of euthanasia, education and learning. Interviewing participants and analysing their responses in regards to the practice of euthanasia explored the cognitive and normative layers of knowledge. Educational theory was used to explain what was happening in relation to an individual's knowledge base regarding euthanasia. The study found that the groups differed in educational background with respect to ethics and the topic of euthanasia with a higher percentage of the health professionals having received education pertaining to ethics and euthanasia. This may explain the fact that five health professionals were able to state a correct definition of euthanasia as opposed to two participants from the general population group. In both groups six of the seven participants were against legalisation of the practice of euthanasia; however, five of the seven participants from the general population group and four of the seven participants representing health professionals were pro euthanasia. Various ways of informal learning contributed to the knowledge base of the participants. Informal learning resulted in all participants being able to discuss issues related to the practice of euthanasia that were relevant, important and related to their value system. In this respect, there was no difference between the two groups. This study has highlighted the difference in knowledge base between health professionals and the general population group. This difference being is the ability to define the term euthanasia. All participants in this study were able to voice opinions on whether euthanasia is practiced and should be practiced or legalised. This study showed that informal learning was important in the acquisition of knowledge and that participants from the general population group were less confident in their knowledge regarding the topic of euthanasia. In view of the findings of this study, it is recommended that since, euthanasia is practiced, an open debate at national level should take place. In view of the ethical issues encountered in everyday living, it is recommended that all New Zealanders are educated regarding ethical issues concerning euthanasia.
Keywords: Euthanasia; New Zealand; Public opinion